The effect of accentuated eccentric load on jump kinetics in high-performance volleyball players - Sheppard, J.; Newton, R.; McGuigan, M. (International Journal of Sports Science and Coaching, 2007)
The purpose of this study was to evaluate the effects of an accentuated eccentric load on subsequent concentric kinetic factors and block jumping performance in elite male volleyball players. Eleven male volleyball high-performance players (18.9 ± 2.6 years, 203.6 ± 5.6 cm, 91.4 ± 8.2 kg), who were training full time with the national team development squad, participated in this within-subject, counter-balanced study. One half of the subjects performed the block jumps (BJ), followed by a 20 kg accentuated eccentric load block jump (AEBJ) condition, whilst the other half of the subject pool performed the testing in the reverse sequence. Superior jump heights (4.3%) and kinetic and kinematic enhancements (9.4, 3.9, 3.1% for peak power, peak force, and peak velocity, respectively) were observed in the AEBJ condition compared to the BJ condition, with no order effect observed. The differences between conditions were statistically significant (p < 0.05), with moderate magnitudes (ES = 0.1-0.4). The results of this study demonstrate that an accentuated eccentric load evokes acute increases in vertical jump height, as well as in the kinetic and kinematic variables that are considered important to vertical jumping ability (force, velocity, and power).